The Effect of Hydrochloric Acid to The Extraction of Gelatin from Salmon Skin - Abdullah, Hasan Zuhudi; Azlan Hisham, Nurdiana (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Gelatin is generated from animal collagen that is mainly from mammalian’ bones. The sources of gelatin frequently do not match the halal standard due to religious considerations. Therefore, fish gelatin has been discovered as an alternative to mammals’ gelatin. This study aimed to produce gelatin from salmon skin, determine the yield at different acid concentrations and times, and identify the properties of the gelatin from salmon skin. The gelatin was extracted from salmon skin at various hydrochloric acid (HCl) concentrations (0.05M, 0.1M, 0.5M, and 1.0M) and times (6 hours, 18 hours, and 24 hours) followed by water extraction (50, 4 hours) and drying (60, 24 hours). The yield of the gelatin at 1.0M (6 hours) is the highest at 38.29%. The possible interactions in the functional group of gelatin were analyzed via Fourier Transform Infrared Spectroscopy (FTIR). Gelatin treated at a high concentration for a short time yields more gelatin and is thus appropriate for industrial application.